New insights into aromatic pathways of carbachlorins and carbaporphyrins based on calculations of magnetically induced current densities; Physical Chemistry Chemical Physics; Vol. 18, iss. 17 - Benkyi I. Isaak; Fliegl H. Heike; Valiev R. R. Rashid Rinatovich; Sundholm D. Dage (2016, 2016)
Title screen